1999
DOI: 10.1074/jbc.274.43.30849
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Insertion in the Hinge Region of Lactose Repressor Protein Alters DNA Binding

Abstract: Amino acid alterations were designed at the C terminus of the hinge segment (amino acids ϳ51-59 The lac repressor (LacI) negatively regulates lac mRNA synthesis by binding with high affinity to its target operator site and thereby precluding transcription by RNA polymerase (1-6). In response to the presence of inducer sugars, LacI undergoes a conformational change that results in diminished affinity for operator sequences without effect on nonspecific DNA binding (1, 2, 7). LacI is a protein of 150,000 Da comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 72 publications
6
60
0
Order By: Relevance
“…It was shown that the mutated subunit formed a heterodimer that did not bind to the receptor in vitro. The uncoupling of a quaternary event and target binding are also supported by recent mutation studies of the Escherichia coli lactose repressor protein (LacI), where it was demonstrated that although assembly and folding of the two functional domains were not significantly affected, their affinity for the DNA target sequence was reduced dramatically (33). These results are consistent with our earlier studies that gonadotropin variants composed of more than 2 subunit domains bind and activate the receptor (21).…”
Section: Biosynthesis Of Hcg Tethersupporting
confidence: 82%
“…It was shown that the mutated subunit formed a heterodimer that did not bind to the receptor in vitro. The uncoupling of a quaternary event and target binding are also supported by recent mutation studies of the Escherichia coli lactose repressor protein (LacI), where it was demonstrated that although assembly and folding of the two functional domains were not significantly affected, their affinity for the DNA target sequence was reduced dramatically (33). These results are consistent with our earlier studies that gonadotropin variants composed of more than 2 subunit domains bind and activate the receptor (21).…”
Section: Biosynthesis Of Hcg Tethersupporting
confidence: 82%
“…We next tested a set of LacI variants expected to have weak affinity for their binding sequences based on previous studies (Falcon and Matthews 1999). Notably, one of these variants, LacI** (see the Materials and Methods), enabled the detection of a lacO array in vivo without interfering with the expression of a neighboring silencer-flanked reporter gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the effects of substitutions on the allosteric transition of this protein, operator release experiments were conducted. Nitrocellulose filter binding was used to monitor decreased levels of bound DNA as a function of inducer concentration (30,31,38,39). Results are presented in Table 3 and Figure 4.…”
Section: Inducibility Of V52 Mutantsmentioning
confidence: 99%